Bioethical aspects in the application of precision medicine in the course of diseases - Quiroz-Arrascue, Xiomara Thalyz (2025)
Precision medicine today is a significant scientific advance in healthcare, but it also poses important bioethical dilemmas. This literature review analyzes the main ethical challenges associated with its implementation, with special emphasis on privacy, autonomy, justice, and equity. Thirty-four relevant studies were reviewed from academic databases such as PubMed, Scopus, Embase, and ScienceDirect, selecting those that addressed ethical implications related to informed consent, the confidentiality of genetic data, equity in access to personalized therapies, and specific challenges in vulnerable populations. The results show a consensus on the need to establish clear regulatory frameworks, promote education in medical ethics, and formulate inclusive public policies. It is concluded that the benefits of precision medicine can only be fully realized by integrating ethical principles that guarantee patients' rights and promote equitable and accessible healthcare for everyone.